2018
DOI: 10.3389/fmicb.2018.00474
|View full text |Cite
|
Sign up to set email alerts
|

Response of Nitrifier and Denitrifier Abundance and Microbial Community Structure to Experimental Warming in an Agricultural Ecosystem

Abstract: Soil microbial community plays an important role in terrestrial carbon and nitrogen cycling. However, the response of the soil nitrifier and denitrifier communities to climate warming is poorly understood. A long-term field warming experiment has been conducted for 8 years at Luancheng Experimental Farm Station on the North China Plain; we used this field to examine how soil microbial community structure, nitrifier, and denitrifier abundance respond to warming under regular irrigation (RI) and high irrigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…With the assembled data sets presently available, we were not able to pinpoint the soil microbial mechanisms underlying positive temperature effects on N 2 O emission at a global scale (Figure 4) (Waghmode et al, 2018). Additionally, enhanced plant growth with increased temperature may increase inorganic nitrogen uptake by the plants, thereby reducing soil nitrogen availability for N 2 O production through nitrification and denitrification (Carter et al, 2012;Dijkstra et al, 2012Dijkstra et al, , 2013Pereira et al, 2013;Zhu et al, 2015).…”
Section: N 2 O Emission Stimulated By Increased Temperaturementioning
confidence: 99%
“…With the assembled data sets presently available, we were not able to pinpoint the soil microbial mechanisms underlying positive temperature effects on N 2 O emission at a global scale (Figure 4) (Waghmode et al, 2018). Additionally, enhanced plant growth with increased temperature may increase inorganic nitrogen uptake by the plants, thereby reducing soil nitrogen availability for N 2 O production through nitrification and denitrification (Carter et al, 2012;Dijkstra et al, 2012Dijkstra et al, , 2013Pereira et al, 2013;Zhu et al, 2015).…”
Section: N 2 O Emission Stimulated By Increased Temperaturementioning
confidence: 99%
“…The amoA gene in ammonia-oxidizing bacteria (AOB) and archaea (AOA) regulates inorganic N availability and N 2 O production via nitrification, while the nirK and nirS genes participate in NO 3 − consumption and N 2 O production, and the nosZ gene mediates conversion of N 2 O to N 2 in the denitrification process. Previous studies reported that elevated temperature did not change the abundance of amoA genes, or found inconsistent responses of AOA and AOB amoA genes to elevated temperature (Liu et al, 2015;Waghmode et al, 2018). Additionally, elevated temperature was found to increase the abundances of nirK and nosZ genes (Kai et al, 2016;Schölkopf & Smola, 2014;Xue et al, 2016), while nirS-containing denitrifiers were reported to be more sensitive to temperature increases than those containing nirK and nosZ genes (Cui et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Plenty of experimental results have shown that global warming has direct impacts on soil microbial respiration, activities, composition and as well as the process rates [4, 5, 12, 13]. However, there is also evidence of indirect effects of climate warming, such as affecting plant photosynthesis and respiration, changing the ratio of carbon and nitrogen nutrition in plants and associated root exudates inputs to the rhizosphere, witch lead to changes in soil microbial community structure [1416].…”
Section: Introductionmentioning
confidence: 99%